[OP.7B.04] UP-REGULATION OF THE NATRIURETIC PEPTIDE CLEARANCE RECEPTOR AND INHIBITION OF LIPOLYSIS BY INSULIN: FILLING THE GAP BETWEEN METABOLIC SYNDROME AND HYPERTENSION. (September 2016) - Bordicchia, M.; Ceresiani, M.; Pavani, M.; Sarzani, R.
Abstract : Objective: Natriuretic peptides (NP), ANP and BNP, regulate not only the homeostasis of the cardiovascular system but also lipid metabolism in adipocytes by promoting lipolysis and thermogenesis. NP circulating levels and therefore their systemic effects are largely dependent on the expression ratio between NPRA (principal biologically active receptor) and NPRC (clearance receptor). Adipocytes affect NP levels and their cardio-renal effects through the expression of NPRC. Aim: To evaluate the role of insulin and ANP on lipolysis, looking for a common mechanism underlying the metabolic syndrome and hypertension. Design and method: The reciprocal regulation of lipolysis by ANP and insulin was evaluated in vitro on primary cultures of adipocytes from visceral adipose tissue (VAT) and on human adipocytes from SGBS cell line (Simpson-Golabi-Behmel syndrome) respectively. The differentiated adipocytes were treated with insulin (100 nM), with or without pre-treatment with wortmannin (100 nM), an inhibitor of PI 3-Kinase, after stimulation or co-stimulation of lipolysis with ANP. The expression levels of the hormone-sensitive lipase (HSL), NPRA and NPRC were simultaneously monitored. Results: Lipolysis, stimulated by ANP and mediated by increased expression of HSL, was inhibited by insulin in a glucose-dependent manner. After an in vitro simulation of cellular "fasting" with a low glucose concentration culture medium, there was no more inhibition by insulin on HSL gene expression and on lipolysis induced by ANP. In differentiated adipocytes there was a potent insulin and glucose mediated stimulation of NPRC expression by the PI3-K way at the basis of the mechanism. No effect was observed on the expression of NPRA. Conclusions: These findings suggest that insulin, in the presence of glucose, limits lipolysis induced by natriuretic peptides' circulating levels and acts as a antilipolytic/lipogenic hormone through the up-regulation of NPRC. Based on preliminary clinical data already presented, these mechanisms should also be active in vivo, unveiling new perspectives about the connection between metabolic syndrome and essential hypertension.